AN ANALYSIS OF FIGURATIVE LANGUAGE IN BLURRYFACE AND TRENCH ALBUMS BY TWENTY ONE PILOTS BAND - Muhammad Bagir; Gurendi Wiwoho (Universitas 17 Agustus 1945 Semarang, 2022)
The aims of this research are to find out and analys the types and meaning of figurative language used in Blurryface and Trench albums by Twenty One Pilots Band, further this research try to compare between the two albums in the use of figurative language. The method of this study is qualitative research. The main data of this research are the lyrics of 5 songs from Blurryface album and 5 songs from Trench album by Twenty One Pilots Band with determined criteria. As a result of the research, the writer found there are fifteen types of figurative language used in both albums, namely metaphor, simile, oxymoron, hyperbole, pun, metonymy, synecdoche, personification, rhetorical question, anaphora, epistrophe, apostrophe, asyndeton, polysyndeton, and polyptoton which is predominated by metaphor (39,71%). Comparatively, there are similarities and differences in the use of figurative language. The both albums similarly describe a feeling of weakness, animate feeling insecure, and express a sense of difficulty. It seems that the two albums are different in the effects expected from the use of figurative language. In Blurryface album, the figurative language is generally used to express feeling of insecure, reflections, and even motivations. Meanwhile, in the Trench album, it is used to illustrate the narrative of the story about the world of Trench, the city of Dema, and the fight of Bandito against the bishops. Keywords: Figurative language, song lyric, figurative meaning, comparative study.